2017
DOI: 10.3390/resources6010007
|View full text |Cite
|
Sign up to set email alerts
|

A Socio-Ecological Approach to GIS Least-Cost Modelling for Regional Mining Infrastructure Planning: A Case Study from South-East Sulawesi, Indonesia

Abstract: Abstract:Regional planning approaches to mining infrastructure aim to reduce the conflict associated with mining operations and existing land uses, such as urban areas and biodiversity conservation, as well as the cumulative impacts that occur offsite. In this paper, we describe a method for conducting Geographical Information System (GIS) least-cost path and least-cost corridor analysis for linear mining infrastructure, such as roads. Least-cost path analysis identifies the optimal pathways between two locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Lechner et al [21] suggested how to optimally design linear infrastructure, such as roads in mines, by considering environmental and social factors. First, environmental and social factors were identified through structured interviews with stakeholders, and the weightings of spatial data inputs were calculated using these factors.…”
Section: Mine Infrastructure Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Lechner et al [21] suggested how to optimally design linear infrastructure, such as roads in mines, by considering environmental and social factors. First, environmental and social factors were identified through structured interviews with stakeholders, and the weightings of spatial data inputs were calculated using these factors.…”
Section: Mine Infrastructure Designmentioning
confidence: 99%
“…This study demonstrates the capability of GIS with LCPA and social survey methods to identify the infrastructure corridors that have the least impact on social and environmental values. This tool has the potential for use and refinement in more effective multiple-criteria decision-making by communities and government planning authorities [21]. Blachowski [22] assessed the following aspects of the mining and transport of rock minerals (aggregates) in the context of regional development: the spatial and temporal changes in the distribution and intensity of mining, availability of economic reserves in active mines, magnitude and distribution of road transport flows of aggregates, potential of railways as an alternative means of transport, and valorization of undeveloped aggregate deposits to assess their suitability for future use.…”
Section: Mine Infrastructure Designmentioning
confidence: 99%
See 1 more Smart Citation
“…These geographic locations are often central to our understanding of these phenomena. Many researchers have shown that spatial proximity affects a variety of trade behaviors, promotes interactions, and thus matters for material flows in the whole life cycle [1][2][3][4][5][6][7]. These are a few examples that reflect a growing interest in spatial concerns within industry ecology.…”
Section: The Importance Of Space In the Industrial Ecologymentioning
confidence: 99%
“…Understanding the linkages between natural and human systems is an important focus for mining and natural resource management disciplines, from conservation to catchment management [6][7][8][9][10]. A better understanding of the interactions between social and environmental systems is crucial in the formulation of sustainable development strategies, especially in the context of mining.…”
Section: Introductionmentioning
confidence: 99%